The use of multiplex real-time PCR improves the detection of the bacterial etiology of community acquired pneumonia - Mustafa Mahmoud, Mohammed Imad Al-Deen; Al-Marzooq, Farah Ibrahim; How, Soon Hin (Malaysian Society of Parasitology and Tropical Medicine, 2011)
Community-acquired pneumonia (CAP) is still a major cause of morbidity and mortality especially to children and compromised hosts, such as the old and those with underlying chronic diseases. Knowledge of pathogens causing CAP constitutes the basis for selection of antimicrobial treatment. Previous data have shown that etiological agents can be identified in only up to 50% of patients, but this figure can be improved by using polymerase chain reaction (PCR). This study was designed to evaluate multiplex real-time PCR as a method for rapid differential detection of five bacterial causes of CAP (Streptococcus pneumoniae, Burkholderia pseudomallei and atypical bacterial pathogens namely Mycoplasma pneumoniae, Chlamydophila pneumoniae and Legionella pneumophila) in CAP patients attending Hospital Tengku Ampuan Afzan (HTAA)/ Kuantan, Pahang, Malaysia. Two previously developed multiplex real-time PCR assays, duplex for the differential detection of S. pneumoniae and B. pseudomallei and triplex for the atypical bacterial pathogens, were used to detect a bacterial cause of CAP in blood and respiratory samples. Thus, 46 blood and 45 respiratory samples collected from 46 adult CAP patients admitted to HTAA were analysed by multiplex real-time PCR assays and conventional methods. The microbial etiology of CAP could be established for 39.1% (18/46) of CAP patients by conventional methods and this was increased to 65.2% (30/46) with the additional use of real-time PCR. The most frequently detected pathogens were S. pneumoniae (21.7% - all by PCR alone), Klebsiella pneumoniae (17.3%), B. pseudomallei (13% - 83% of them positive by PCR alone and 17% by both culture and PCR), Pseudomonas aeruginosa (6.5%), M. pneumoniae (6.5% - all by serology), C. pneumoniae (4.3% - all positive by both PCR and serology), L. pneumophila (2.1% - all by PCR alone), Escherichia coli (4.3%). Haemophilus infuenzae, Acinetobacter lwoffii and Acinetobacter baumannii were detected by conventional methods (2.1% for each).